Pharmacokinetic Evaluation of a 1-Day Treatment Initiation Option for Starting Long-Acting Aripiprazole Lauroxil for Schizophrenia. Issue 5 (October 2018) - Hard, Marjie L.; Wehr, Angela Y.; Du, Yangchun; Weiden, Peter J.; Walling, David; von Moltke, Lisa
Abstract: Background: Aripiprazole lauroxil (AL), a long-acting injectable antipsychotic for the treatment of schizophrenia, requires 21 days of oral aripiprazole supplementation upon initiation. We report findings from a phase 1 study investigating a nanocrystalline milled dispersion of AL (ALNCD ) as a potential 1-day initiation regimen. The 1-day initiation regimen is designed to enable rapid achievement of plasma aripiprazole concentrations that are comparable with the 21-day oral initiation regimen. Here, a 6-month pharmacokinetic study compared 2 different initiation regimens for starting AL. Methods: Patients were randomized 1:1:1:1 to receive 1 of 4 treatments consisting of the 1-day (single ALNCD injection + one 30-mg dose of oral aripiprazole on day 1 only) or the 21-day (15-mg daily dose of oral aripiprazole for 21 days) initiation regimen, each combined with a starting AL dose of either 441 mg or 882 mg. Results: In total, 133/161 patients completed the study. The pharmacokinetic profile of the 1-day initiation regimen was comparable to the 21-day initiation regimen; both achieved aripiprazole concentrations in the therapeutic range within 4 days and remained in a comparable concentration range during treatment initiation. Common adverse events (≥5.0%) were injection-site pain, headache, increased weight, insomnia, dyspepsia, and anxiety. Nine akathisia events occurred (4 events in 4 patients and 5 events in 2 patients in the 1-day and 21-day initiation regimen groups, respectively). Conclusions: The 1-day initiation regimen resulted in plasma aripiprazole concentrations consistent with the 21-day initiation regimen. Therefore, a single dose of ALNCD with a single 30-mg oral dose of aripiprazole provides an alternative initiation regimen for starting AL. Abstract : Supplemental digital content is available in the text.